The New York State Minority Health Survey: Determinants of Oral Health Care Utilization - Amit Chattopadhyay, BDS, MDS, MPH, PhD; Jayanth V. Kumar, DDS, MPH; Elmer L. Green, DDS, MPH (Blackwell Synergy, 2003)
To determine the factors associated with visits to a dentist and more specifically the role of dental insurance coverage and to explore the reasons for not visiting a dentist among minorities in New York State